Knowledge of Balanced Nutrition among High School Students in Makassar City South Sulawesi - Hanifah, Astin Nur; Pannyiwi, Rahmat; Wahyuni, Tri; Ramli, Rachmat; Putra, Egy Sunanda (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Fulfillment of balanced nutrition plays an important role in influencing a person's health. One of the factors that can affect a person's nutritional state is nutritional knowledge and its application in everyday life. Adolescence is a transition period from children to adulthood. At this time there is an increase in the need for growth and development so that optimal nutritional intake is needed. However, until now there are still many adolescents who have nutritional problems. One of the causes of undernutrition is the lack of knowledge of adolescents about balanced nutrition. The purpose of the study was to determine knowledge about balanced nutrition in adolescents. This research was conducted in a senior high school. This research method is an observational quantitative research with a cross sectional study design. Data collection was done online by sending a google form link. The results showed that most respondents still had insufficient knowledge of balanced nutrition, which amounted to 53.5%. It is concluded that the school is expected to conduct education about balanced nutrition regularly so that students' knowledge of balanced nutrition increases.